New Approaches to Arteriovenous Fistula Creation - Rajan, Dheeraj K. (Seminars in Interventional Radiology, 2016)
An autogenous arteriovenous fistula is considered the ideal access for hemodialysis delivery. However, surgical creation of an arteriovenous fistula is associated with less than optimal technical success, and multiple interventions are often required to assist maturation or maintain early patency. Given these shortcomings, multiple new approaches are now under investigation that possibly improve on surgical techniques and/or outcomes. Minimally invasive methods of creation with novel devices are under investigation, with preliminary published results available.
Keywords: arteriovenous fistula; dialysis; creation; surgery; interventional radiology